Design of a Shallot Peeling Machine for EA Kitchen MSME Using Voice of Customer, Quality Function Deployment, and Anthropometric Analysis - Indah Putri Herlambang; Wiwin Widiasih (Jurnal Ilmiah Teknik, 2026)
Manual shallot peeling remains a time-consuming and labor-intensive activity in small-scale food-processing enterprises. Therefore, appropriate peeling equipment is needed to improve efficiency while remaining suitable for the operational conditions of micro, small, and medium enterprises (MSMEs). Objective: This study aimed to develop a user-oriented shallot peeling machine design that meets the operational, ergonomic, and economic requirements of EA Kitchen, a food-processing MSME located in Driyorejo, Gresik, Indonesia. Methods: This study employed a product design and development approach. Data were collected through field observations, interviews, questionnaires, and anthropometric measurements. User requirements were identified using the Voice of Customer (VoC) approach and translated into technical priorities through Quality Function Deployment (QFD) and the House of Quality (HoQ). Anthropometric analysis was used to determine the appropriate machine height, while preliminary cost analysis was conducted to estimate fabrication requirements. Results: The results showed that design was the highest-priority customer attribute, with a weight of 47.3%, followed by quality at 31.5% and safety at 21.0%. Large capacity was identified as the most important technical response at 31.49%, followed by ease of maintenance at 28.03%, ease of operation at 21.80%, and material selection at 18.69%. The proposed machine height was 83 cm, while the preliminary cost of the identified main components was IDR 900,000. Implications: The findings provide a practical basis for developing a shallot peeling machine that is more compatible with the production capacity, ergonomic requirements, operational simplicity, and financial limitations of small-scale food-processing enterprises. Originality: The originality of this study lies in the integration of VoC, QFD, anthropometric considerations, and cost evaluation into a single user-centered design framework specifically applied to the development of shallot-peeling equipment for MSMEs.